Anosmia, Dysgeusia, and Comorbidity in COVID-19 Patients with Respiratory Tract Manifestations - Jason Lefranda Jocelino Siswanto; Viskasari Pintoko Kalanjati; Soetjipto Soetjipto; Azlin Muhammad Mohd Yasin (Jurnal Respirasi, 2023)
Introduction: Olfactory and special sensory disturbances such as anosmia and dysgeusia have been found among COVID-19 patients. These manifestations may cause post-covid sequelae, disturbing patients' quality of life who have recovered from COVID-19. This study aimed to analyze the association between anosmia and dysgeusia with the comorbidities in adult COVID-19 patients admitted to Dr. Soetomo General Hospital, Surabaya, from 1 January 2020 to 30 September 2021. Methods: This was a cross-sectional retrospective analysis study based on the medical records of all patients who met the criteria (n = 158). The minimal age inclusion was 18 years old, and the patient must be positively diagnosed with COVID-19 (reverse transcription polymerase chain reaction/RT-PCR). Results: Out of 158 patients, all had a fever, and approximately 93% of patients showed respiratory signs and symptoms. There were 128 patients (81%) who suffered from anosmia, and 15 patients (9.5%) had dysgeusia. Significant associations were found between anosmia with dysgeusia (p = 0.049) and between anosmia with cough (p = 0.003) and dyspnea (p = 0.000). The predominant comorbidities reported were overweight (60%), hypertension (42%), and type-2 diabetes mellitus (37%). Conclusion: There were significant associations between anosmia with dysgeusia and the respiratory tract signs and symptoms instead of the comorbidities reported.